Slender Roof Structures - Failure Reviews and a Qualitative Survey of Experienced Structural Engineers. (August 2018) - Klasson, Anders; Björnsson, Ivar; Crocetti, Roberto; Hansson, Eva Frühwald
Abstract: Many slender roof structures have collapsed due to snow loading and instability. Although accurate stability calculations can be performed using theoretical models, these calculations may not always reflect the behaviour of real structures as a result of the uncertainties relating to e.g. loading, material behaviour, geometry, initial imperfections and the actual boundary conditions of the structure. As a result, the approach to stability design requires subjective decisions by the structural engineer concerning loading and modelling assumptions. This paper investigates the significance of these types of decisions made by structural engineers in designing slender roof structures. This investigation is based on a review of previous failure studies together with a survey of 17 experienced structural engineers. The results of this investigation indicate that most structural failures are a result of human errors; thus, a suitable strategy for avoiding errors is through quality control and design checking. Moreover, a significant discrepancy was observed concerning design assumptions made by the engineers in the study. Some of these assumptions, e.g. a non-conservative choice of the buckling length of a beam, have a significant negative impact to structural safety. It is therefore recommended that the structural engineers involved in the design of a structure have adequate experience and a holistic mindset. Another recommendation is that both drawings and design calculations are thoroughly reviewed before construction. Also, temporary bracing to be used during construction should be included in design. Finally, it is important that the communication between different partners in the design of a structure is satisfying.